ANALISIS BIAYA PEMANENAN DAN PRODUKTIVITAS PRODUKSI KAYU EKALIPTUS (STUDI KASUS: HPHTI PT.PSPI DISTRIK PETAPAHAN) - Santa Fermana, Jesica; Sadjati, Emy; Ikhwan, Muhammad (Fakultas Kehutanan Universitas Lancang Kuning, 2019)
Industrial plantations are production forests that have monoculture species (1 species), which take up to 5 years to be ready for harvest. Before harvesting, activities are carried out it is necessary to analyze the cost of harvesting,where the aim is to find out the magnitude of the profits obtained by the company. The purpose of this study is to analyze the cost of harvesting and analyze the productivity of wood from harvesting activities at HPHTI PT. PSPI Petapahan District. This research was conducted in May - June 2019. The sampling method in this study used a purposive sampling system. Based on the results of research conducted at PT. PSPI Petapahan District, the production costs for harvesting are activity are obtained, the amount of costs for felling and dividing the stems of IDR 27.235/hour, the costs for stacking IDR 200.584/hour, costs for stripping bark of IDR 203.991/hour, costs for skidding IDR 204.091/hour, the fee for loading and unloading skid is IDR 200.584/hour and the cost for loading to truck is IDR 200.584/hour. While harvesting productivity for each activity is felling productivity of 20,97 m3/hour, division of stems of 35,25 m3/hour, stacking of 21,10 m3/hour, stripping bark of 39,50 m3/hour, skidding of wood by 21,23 m3/hour, skid loading and unloading of 49,61 m3/hour and loading to trucks of 12,40 m3/hour.